A água e a cartografia do imaginário nos climas de três territórios geográficos - Nora, Giseli Dalla (2018)
The bridges symbolize dialogue, and I have tried to build several bridges in the construction of the thesis, such as the relativization of the ISOLATED-I to group research through a COLLECTIVE-US, as well as the essence of geography, now impregnated with pedagogical cultures in the experiences, research and awareness of environmental education. This research is based on the principles of climate justice, including the different perceptions about the climate in 3 different territories, which had characteristics of fresh water, salt water and water scarcity. For these contexts, small geographic territories were privileged: in the Mato Grosso Pantanal of abundant freshwater bodies [farmers / farmers of São Pedro de Joselândia]; in the Cerrado of the Brazilian Midwest already with water scarcity [farmers / farmers of the quilombo Mata Cavalo]; and in the northern and maritime portion of Spain [fishermen and seafarers living in Galicia]. Listening to stories and telling others, I tried to build more bridges of dialog between environmental education and climate justice, dimensions that are quite absent in studies on climate change, especially in the global milestones proposed by the United Nations. The methodology of this work is the Sato´s Cartography of the Imaginary as a guide for the course of research and political positioning. The methodology adopted is a way of interpreting the phenomena, for understanding that the ideological choices are not neutral, elucidating the research territories in detail with case studies, dialoguing about experiences and experiences. In the cartography of the results, the scarcity of water is perceived by the Pantanal inhabitants as a threat of the plantations, since the change in rainfall regimes has already been forging changes in the landscapes of fresh water. In the bridges built in the Cerrado (savanna), the increase in temperature and the scarcity of drinking water are the climatic injustices that also affect the gardens, in addition to changing eating habits and health problems. I also observed that access to water is linked to the Hick and Artesian wells, and that, soon, may further aggravate the social and environmental conflict already existing in the locality. The quilombo Mata Cavalo (community of black descendant slaves) has other dilemmas related to the ethnic-racial condition, which further intensifies the management situation of its territories. I also discuss the impressions about Galicia, salt water territory that I had the opportunity to explore during the doctoral “sandwich” (part time oversea PhD). I learned about "fishing gear", species-specific fishing practices, and how the vulnerability of fishermen and sea workers is present when we explore climate change. Access to potable water is not yet a concern, however they are worry about changes in ocean. At this point, my perceptions show the phenomenon of climate change and its impacts on a local scale, identifying three levels of vulnerability: a) scientific and pedagogical - for understanding and communicating what climate change is and what they represent; b) physical and environmental conditions - related to access to water, changes in temperature as well as changes in rainfall regimes, and c) public policies - with broad social inclusion, including nonhuman lives. This research supports the thesis that, far beyond the proposals of adaptation and resilience, it is urgent to understand the unequal development generated by consumption models. For this reason, the research recognizes the need to change the system, not the climate. I believe in the power of environmental education to promote resistance against a society that exploits nature to its exhaustion, amalgamated by the hope of the peoples' well-being and the care of their environments.